2010
DOI: 10.1158/1055-9965.epi-09-1282
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of VIA (Visual Inspection of the Cervix After Acetic Acid Application) Positivity in Cervical Cancer Screening of Women in a Peri-Urban Area in Andhra Pradesh, India

Abstract: Objectives: Visual inspection of the cervix after acetic acid application (VIA) is widely recommended as the method of choice in cervical cancer screening programs in resource-limited settings because of its simplicity and ability to link with immediate treatment. In testing the effectiveness of VIA, human papillomavirus DNA testing, and Pap cytology in a population-based study in a peri-urban area in Andhra Pradesh, India, we found the sensitivity of VIA for detection of cervical intraepithelial neoplasia gra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
50
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 18 publications
8
50
2
Order By: Relevance
“…One of the important determinants for positive VIA testing is clinical symptoms of patients (symptomatic or asymptomatic). Cervical infection or inflammation, and area of transformation zone which is affected by age, menopausal status, parity and route of delivery have been shown to affect the result of VIA testing (Vedantham et al, 2010;Cremer et al, 2011;Castle et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…One of the important determinants for positive VIA testing is clinical symptoms of patients (symptomatic or asymptomatic). Cervical infection or inflammation, and area of transformation zone which is affected by age, menopausal status, parity and route of delivery have been shown to affect the result of VIA testing (Vedantham et al, 2010;Cremer et al, 2011;Castle et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Cervical cells were collected from women for cytological and virological investigation, and the cervix was examined with naked eye visual inspection after application of acetic acid (VIA). We found that a positive VIA reading (presence of an acetowhite lesion in the cervical transformation zone) had a surprisingly low sensitivity (26.3%) and moderate specificity (76.4%) for the detection of cervical neoplasia (9,28).…”
mentioning
confidence: 80%
“…Cervical cells were collected from women for cytological and virological investigation, and the cervix was examined with naked eye visual inspection after application of acetic acid (VIA). We found that a positive VIA reading (presence of an acetowhite lesion in the cervical transformation zone) had a surprisingly low sensitivity (26.3%) and moderate specificity (76.4%) for the detection of cervical neoplasia (9,28).Given the large number of false-positive VIA readings, we inquired if these lesions might be occurring as a result of infections with Epstein-Barr virus (EBV) or cytomegalovirus (CMV), prevalent latent herpesviruses which are known to be shed from the female genital tract (2, 6, 14, 21). We also examined whether cervical EBV and CMV detection correlated with either cervical HPV detection or other markers of cervical pathology, since these viruses have been postulated to have a possible cocarcinogenic role with human papillomavirus (HPV) for cervical neoplasia (19, 23).…”
mentioning
confidence: 83%
“…Many of these countries have limited funds and capacity for large, widespread screening programs. Those countries that are building capacity for cervical cancer prevention rely mostly on point of care testing and treatment using strategies such as visual inspection with acetic acid (VIA) [10][11][12][13][14]. Although these strategies are better than no strategy, widespread capacity for screening and appropriate follow-up in many of these regions are limited, particularly in rural areas.…”
Section: Impact Of Screening and Prevention For Cervical Cancermentioning
confidence: 99%